Association between internal migration experience and depressive symptoms: analysis of PSID data - Liao, Zi-Xuan; Tan, Xiao-Min; Zhao, Ying-Ying; Sun, Xiao-Cui; Yi, Fa-Ling (BMC public health, 2023)
Depression is on the rise globally. Additionally, the United States has a high level of population mobility. The main aim of this study was to provide a reference for improving the mental health of internal migrants by investigating the relationship between internal migration experience and depressive symptoms. We analysed data from the Panel Study of Income Dynamics (PSID). We included PSID data from the 2005 to 2019 waves in which all respondents were asked about their internal migration experience and depressive symptoms. This study included 15,023 participants. T tests, chi-square tests, multiple logistic regression methods were performed and fixed effects model. In the sample, the prevalence of depressive symptoms was 4.42%. The risk of depression in internal migrants was 1.259 times (OR = 1.259, 95% CI = (1.025-1.547, p < 0.05) that of nonmigrants. Internal migration experience was significantly positively associated with female depressive episodes (OR = 1.312, 95% CI = 1.010-1.704, p < 0.05) and increased risk of becoming depressed at a young age (OR = 1.304, 95% CI = 1.010-1.684, p < 0.05). The association between internal migration experience and depressive symptoms was more significant for participants who might move (OR = 1.459, 95% CI = 1.094-1.947, p < 0.05). In addition, different internal migratory causes are associated with depressive symptoms to varying degrees. Our findings highlight the need for greater policy attention to mental health inequalities between Internal migrants and those who never move away from their hometown in the United States. Our study provides a foundation for further research.